Blood lactate profile when highly qualified swimmers perform a special serial test - Kolganova E.Yu.; Golushko T.V.; Fetisov V.N.; Gridneva E.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assessment of the relationship between the lactate profile and the level of development of special endurance, which determines the competitive results of highly qualified swimmers. Methods and structure of the study. Athletes performed a serial swimming test 8x200 m in a 5-minute mode with intensity from low to maximum. The values ​​of the rate of lactate accumulation in the blood determined the nature of the curve depending on the swimming speed. Lactate tolerance was defined as the differential rate between blood lactate concentrations of 5.0 and 10.0 mM (LT 5–10). Results and conclusions. Analysis of blood lactate levels obtained during the 8x200m swim test revealed significant improvements in endurance performance over a one-year training cycle. Improvement in lactate parameters is associated with an increase in maximum 200 m swimming speed under training conditions; the relationship between the blood lactate profile and changes in competitive results is insignificant.